2011
DOI: 10.1038/emboj.2011.412
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of translocation polarity by helicase domain 1 in SF2B helicases

Abstract: Regulation of translocation polarity by helicase domain 1 in SF2B helicasesBiochemical and reverse footprinting studies of the nucleotide excision repair protein XPD show that opposing translocation polarity in superfamily II A and B helicases is an intrinsic property of their respective motor domains, rather than related to different relative DNA binding orientations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
90
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(102 citation statements)
references
References 38 publications
11
90
0
1
Order By: Relevance
“…In support of our model, recent studies on the entire reconstituted human TFIIH complex also suggested recognition of strongly helix-distorting cisplatin as well as Cy3 adducts on the translocated strand (28). Based on crystallographic and biochemical data in combination with mutational analyses, a structural model has been suggested of how XPD interacts with DNA to recognize lesions (10,11,42). In this model, DNA interactions with amino acid residues along a channel in XPD direct the translocated ssDNA through a pore in the enzyme (see also below).…”
Section: Uvrb and Xpd Helicase Activities Are Activated By Proteinmentioning
confidence: 64%
“…In support of our model, recent studies on the entire reconstituted human TFIIH complex also suggested recognition of strongly helix-distorting cisplatin as well as Cy3 adducts on the translocated strand (28). Based on crystallographic and biochemical data in combination with mutational analyses, a structural model has been suggested of how XPD interacts with DNA to recognize lesions (10,11,42). In this model, DNA interactions with amino acid residues along a channel in XPD direct the translocated ssDNA through a pore in the enzyme (see also below).…”
Section: Uvrb and Xpd Helicase Activities Are Activated By Proteinmentioning
confidence: 64%
“…Several lines of evidence lead to the currently accepted hypothesis that the lesions are initially recognized by XPC with the help of UV-DDB (UV DNA damage binding protein) for cyclobutane pyrimidine dimer (CPD) lesions (17)(18)(19)(20) followed by damage verification by XPD/TFIIH (21)(22)(23)(24), XPA, and XPG (3) to finally assemble to the preincision complex (3,(25)(26)(27). This step seems to involve recruitment of the XPA protein, which is one of the proteins essential for both GG-NER and TC-NER (28).…”
mentioning
confidence: 99%
“…The iron-sulfur and arch domains together with helicase domain 1 comprise a narrow pore with ϳ1-nm diameter (8,9). In addition, the crystal structure of taXPD in complex with a short stretch of ssDNA, as well as reverse footprinting analysis, have led to a model of the possible path of the DNA across the enzyme (11,18). In this model, the DNA threads through the protein pore and is in close proximity to the iron-sulfur cluster, consistent with a proposed role of such clusters in DNA damage investigation (19 -23) and the recent identification of a dedicated lesion recognition pocket near the pore (12).…”
mentioning
confidence: 99%